Can healthy life style predict successful aging among Iranian older adults? - Shafiee, Mohsen; Hazrati, Maryam; Motalebi, Seyedeh Ameneh; Gholamzadeh, Sakineh; Ghaem, Haleh; Ashari, Asmidawati (Tehran University of Medical Sciences, 2020)
Background: Successful aging is a prominent and worldwide theme in gerontology. However, until recently, only few studies were conducted about successful aging in Iran. This study examined whether a healthy lifestyle could predict successful aging among older Iranians. Methods: This cross sectional and descriptive study included 975 older Iranians who were selected through a multistage cluster-quota method from the health centers of Shiraz, Iran. A 5-part questionnaire, including demographic characteristics, the Seniors' Healthy Lifestyle, Barthel Index, the Diner Life Satisfaction and Quality of Life, was used to collect the data. A logistic regression analysis was used in data analysis; data were analyzed using SPSS 21; and significance level was set at α = 0.05. Results: The prevalence of successful aging among older Iranians was calculated at 24.0%. Results of multiple logistic regression analysis revealed that age (95% CI = 1.129- 1.702 and OR = 1.352), gender (95% CI = 0.412-0.764 and OR = 0.687), education level (95% CI = 1.443 - 1.699 and OR = 1.454), job (95% CI = 1.063-1.413 and OR = 1.185), monthly income (95% CI = 1.355-4.055 and OR = 2.272), insurance (95% CI = 0.344-0.842 and OR = 0.540), source of income (95% CI = 1.014-1.298 and OR = 1.145), and healthy lifestyle (95% CI = 0.772 - 0.858 and OR = 0.814) were predictors for successful aging. Conclusion: Findings indicated that successful agers were mostly younger men, with higher education level and monthly income, who had insurance and a job and a healthy lifestyle. Thus, to age successfully, one must maintain and improve healthy lifestyle to prolong one's health.